The middle-level teacher technology guidebook : 20 questions and 260 answers - Brinthaupt, Thomas M., 1958-; Brinthaupt, Thomas M., 1958-; Lipka, Richard P. (Instructional technology guidebooks for educators and parents, 2019)
This guidebook is designed to be the middle-level teacher's friend in addressing a wide variety of questions regarding the use of educational and instructional technologies. It can serve as a companion and guide through the myriad challenges and opportunities related to the effective use of technology in one's classroom and school.A sample of middle level U.S. teachers provided us with detailed answers about their experiences with using technology in their teaching. Specifically, they shared their challenges, barriers, ideas, and suggestions for working successfully with administrators, technology specialists, students, fellow teachers, and parents when teaching with technology. We have organized the teachers' experiences and recommendations according to each stakeholder.Rather than recommending or reviewing specific educational technology companies, applications, or tools, we provide a large number of strategies that are "built to last" and should be applicable regardless of the specific tool under consideration. We assume that it doesn't ultimately matter what the tool or technology is that you're using--it's how and why you're using it for teaching and learning that will determine whether it is successful or not. The "how" and "why" aspects encompass the built-to- last strategies included in this guidebook.